PREVALENCE OF CASES OF CHILD ABUSE AND THEIR IMPACT ON PERFORMANCE OF SECONDARY SCHOOL PUPILS IN ZIMBABWE: A CASE STUDY OF NKAYI DISTRICT - Thembinkosi, Tshabalala (IJRDO- Journal of Educational Research, 2018)
Cases of child abuse are reported year in and year out in Zimbabwe with little signs of the phenomenon abating. Child abuse is when a parent, caregiver, adult, sibling, classmate or any other person more powerful than the victim, whether through action or failing to act, causes injury, death, emotional harm or risk of serious harm to a child. Child abuse usually refers to unfair, cruel or violent treatment of a child in a physical, sexual and emotional way, including child labour such that the victim’s rights are threatened and for school children, it significantly affects their learning. The study employed the quantitative methodology using a sample of 400 form three and form four pupils randomly selected from the thirty secondary schools in Nkayi District of Zimbabwe’s Matabeleland North Education Province. The study utilised the questionnaire to collect data from the respondents. The study revealed that child abuse was prevalent in Nkayi District and yet most school authorities were not doing enough to eradicate it. Most of the students in the sample had themselves been victims of one form of abuse or the other. The researcher recommends that school heads, teachers, pupils and parents should work together to expose, prevent and report all cases of abuse of children to avoid emotional and physical damage to the children.